The effects of heart rate variability biofeedback on functional gastrointestinal disorders: a scoping review - Pereira, Ashley G.; Fu, Lily; Xu, William; Gharibans, Armen A.; O’Grady, Greg (Frontiers in Physiology, 2025)
BackgroundFunctional Gastrointestinal Disorders (FGID) are a group of symptom-based disorders that occur across the alimentary tract and have a high prevalence globally in both adults and children. These symptoms are chronic and/or recurrent and often have substantial effects on quality of life. Their incidence is tied to multiple factors, including gut-brain axis imbalance, which includes autonomic dysregulation related to a relative withdrawal of vagal activity. Heart rate variability biofeedback (HRVB) is a non-invasive intervention that can influence autonomic activity and has shown benefit for diverse conditions including depression and anxiety, however the evidence of its effect has not yet been systematically assessed in FGIDs. This scoping review aimed to collate and evaluate the available literature regarding HRVB and FGIDs.MethodsWe systematically searched four medical databases. Four interventional studies using HRVB in FGIDs met inclusion criteria.ResultsStudies were heterogeneous, including both paediatric and adult patients, as well different subtypes of FGID. Two of the four studies demonstrated significant symptom improvements from HRVB while the other two found no significant difference.DiscussionOur findings suggested that at least 6 weeks of HRVB is required to observe an impact on FGID symptoms. We provide recommendations for future studies of HRVB in FGIDs, which are needed. Evidence on HRVB for FGID is still emerging, but appears promising when administered optimally.